Ex-Situ Study on Density Dependent Survival after Handling Yolk Sac Larvae of Snow Trout, Schizothorax plagiostomus Heckel - Bahuguna, S.N.; Negi, R.S.; Upadhyay, M.K. (Our Nature, 2010)
Snow trout, Schizothorax plagiostomus (Heckel) is most important commercial food fish of Garhwal Himalaya inhabited among the snow fed tributaries of river Ganga. In present study the induced breeding were carried out by stripping method and it was noticed that the survival of larvae were high, near (95-100%), at high density and the lowest survival rate was observed at the lowest density (less than 5%). The mechanism responsible for the observed density dependent survival was not under stood. It is possible that the concentration of substance secreted by larvae as well as change in larval behaviors is responsible factors for survival in higher concentration. Key words: Survival, Schizothorax plagiostomus, density, Garhwal Himalaya DOI: 10.3126/on.v7i1.2562 Our Nature (2009) 7:146-150